Genetic improvement of underutlised legumes - Naiken-Ó Lochlainn, Karmeswaree Govinthan (2011)
In today's world of rapidly changing climates, ever-increasing human population growth and increased competition for space, the production of energy and high quality food to meet increasing demands presents an enormous challenge to the related industries. It has been predicted that global food production alone, must increase by 70% by 2050 to prevent worldwide starvation. The application of plant biotechnology offers a promising alternative over classical crop improvement techniques in the development of breeding programmes that could respond rapidly to future demands for high-yielding and nutritionally-enhanced crops. Adopting such strategies to underutilised legume crops represents a viable avenue for crop improvement, especially in developing countries with a high incidence of poverty and malnutrition, where local environmental conditions frequently prove too challenging for effective cultivation of commercial cultivars. The main objective of this thesis was to generate fundamental data regarding the adoption of tissue culture-based transformation strategies for the genetic improvement of two such crops, jicama [Pachyrhizus erosus (L.) Urban] and Bambara groundnut [Vigna subterranea (L.) Verdc.]. The work carried out on jicama investigated the regeneration potential of this plant in vitro as a basis for future biotechnological techniques. Preliminary tissue culture experiments identified explant types and plant growth regulator (PGR) matrices and concentrations that produced optimal regenerative responses in vitro. Histological analysis of regenerated tissue revealed that shoot formation occurred via somatic embryogenesis. Possible avenues for further optimisation of the explant-to-plant regeneration protocol, for downstream molecular genetic applications, were explored and discussed. For Bambara groundnut, this study initially focused on developing a novel explant-to-plant regeneration system, previously not reported for landraces DipC, Uniswa-Red and S 19-3, through the adoption and modification of techniques specific for distinct Bambara landraces. This micropropagation protocol employed whole zygotic embryos as starting explants, which formed the basis for subsequent transformation studies. Genetic transformation was attempted via biolistic- and Agrobacterium-mediated approaches, using transformation vectors pVDH65, pB1l21, harbouring the nptII selectable marker and uidA (gus) reporter genes, while pBIl21-LeB4-Ber e I additionally carried the methionine-rich ber el gene. T-DNA transfer in transformed explants was confirmed via histochemical GUS analyses, while peR assays identified putatively transformed regenerated shoots. Explant viability was significantly compromised following bombardment or inoculation, resulting in reduced shoot regeneration, and thus limited the production of transgenic plants. Improvements in transformation efficiency and regeneration frequency were made following protocol optimisation, and the potential for further improvements to efficiently produce well-developed, healthy transgenic shoots were explored and discussed. The results presented in this thesis describe the optimisation of innovative tissue culture and regeneration protocols, which form a fundamental prerequisite to future transformation-based experiments for jicama and Bambara groundnut. Additionally, previously unpublished data generated from transformation studies in Bambara groundnut has revealed its potential for genetic manipulation. These results have established the foundation of novel micropropagation and transformation systems with the potential to be further optimised to genetically enhance and exploit the enormous agronomic potential of these underutilised legume crops.